Biochemical Properties of the Acid Ectophosphatase Activity of Phytomonas serpens Involved in Cell Proliferation - Luiz Fernando Carvalho-Kelly; Anita Leocadio Freitas-Mesquita; Thaís Souza Silveira Majerowicz; José Roberto Meyer-Fernandes (Kinases and Phosphatases)
Phytomonas is the only kinetoplastid that can parasitize plants, causing economically relevant issues. Phytomonas serpens share similarities with pathogenic trypanosomatids, including surface enzymes that are involved in adhesion to the salivary gland of their experimental host, the insect Oncopeltus fasciatus. Ectophosphatases are cell surface enzymes involved in host–parasite interactions that are widely distributed among microorganisms. This work aimed to perform the biochemical characterization of P. serpens ectophosphatase activity, investigating and discussing its possible physiological role. This activity presented an acidic profile, and its kinetic parameters Km and Vmax were calculated as 1.57 ± 0.08 mM p-NPP and 10.11 ± 0.14 nmol p-NP/(h × 108 flagellates), respectively. It was stimulated by cobalt, inhibited by zinc, and insensitive to EDTA, a divalent metal chelator. The inhibitor sodium orthovanadate was able to decrease P. serpens ectophosphatase activity and growth, suggesting its involvement in cell proliferation. Given that P. serpens can uptake inorganic phosphate (Pi) from the extracellular medium, it is likely that its ectophosphatase activity acts together with the transport systems in the Pi acquisition process. The elucidation of the molecular mechanisms involved in this process emerges as a relevant perspective, providing new strategies for controlling Phytomonas infection.